Cardiorenal syndrome: review of our current understanding. (January 2016) - Hadjiphilippou, Savvas; Kon, Sui Phin
Renal and cardiac diseases are both prevalent and carry significant morbidity and mortality. They share common vascular risk factors and are physiologically interlinked. Dysfunction in one organ affects the other. Concurrent renal and cardiac disease is associated with a poor prognosis. This close relationship is reflected through cardiorenal syndrome. A classification system has been proposed; however, the underlying process is complex and multifactorial. Management of this syndrome focuses on improving heart function, reducing volume overload, and managing heart failure and chronic kidney disease. This, however, is challenging, limited by paucity of evidence and may lead to suboptimal therapy. Increased recognition of this syndrome should raise awareness in providing early therapy and avoiding adverse outcomes due to under-treatment. In this article, we provide an overview of our current understanding of cardiorenal syndrome, as well as its pathophysiology and treatment options.